Produção de citocinas por células mononucleares humanas estimuladas por formas amastigotas de Leishmania(Viannia) braziliensis - Gomes, Clayson Moura (2012)
Introduction: Leishmaniasis is a tropical zoonoses that is endemic, causing different clinical forms including cutaneous, diffuse, disseminated, mucosal and visceral manifestations. The L. (V.) braziliensis is the most common parasite found in cutaneous leishmaniasis in Brazil and is the major agent for the mucosal leishmaniasis. The manifestation of the disease and the clinical forms are dependent on several factors related between the parasite and host. Objective: The aim of this study was to compare the ability of amastigote parasite isolated from patients with cutaneous or mucosal leishmaniasis to stimulate the production of cytokines in peripheral blood mononuclear cells cultures (PBMC) obtained from health donors. Methods: Isolates of patients with cutaneous or mucosal lesion were inoculated in IFNγ knockout mice to obtain amastigotes, which were purifyed by density using Percoll. The PBMCs from healthy individuals were separated by density using Ficoll. The cells were incubated in cultures at different times with amastigotes and then the supernatant were collect to quantify cytokines by ELISA or cells that are used to quantify cytokines using the real time PCR. Results: PBMCs produced higher amounts of IL-1β, IL-6, IL-10 and TGFβ in cultures after stimulation with amastigotes than uninfected controls. When comparing isolates from cutaneous or mucosal disease it was not found differerence regarding to the production of IL-6, IL-10 and TGFβ, but amastigotes from patients with cutaneous leishmaniasis induced more IL-1β than in parasites obtained from mucosal lesion. Production of IFNγ IL17, and TNF was was not detected at different times after stimulation with L. (V.) braziliensis amastigotes. Conclusion: The results suggest that amastigotes of patients with cutaneous leishmaniasis interact with innate immunity cells by inducing the production of proinflammatory or anti-inflammatory and isolated from mucosal lesions induce less IL-1 than parasites obtained from skin lesions. The greatest amount of IL-1 promotes an inflammatory response with migration of cells to the site of infection, so a low xvii production would cause a slower disease and would prejudice an effective acquired response. Thus, the parasite would be able to survive longer in host in a silent way.